Pendampingan Pengisian Aplikasi P-Care BPJS Di Fasilitas Kesehatan Tingkat Pratama (FKTP) - Asti Nurhayati; Reza Al Afsyar K; Adelia Cahya U; Nabilla Tri P (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2022)
P-Care BPJS Health is a web-based patient service information system application provided by BPJS Health intended for primary health facilities to provide easy data access to BPJS servers, both registration, diagnosis, therapy, to laboratory services. P-Care was introduced throughout Indonesia in early 2014. The P-Care application has been implemented since 2014, but its use has not been optimal due to several things, one of which is the frequent errors in the P-Care application, namely P-Care officers at health facilities often experience problems when entering BPJS patient data, causing officers perform double entry of BPJS patient data. The purpose of this activity is to assist officers in optimizing the use of the BPJS P-Care application. The method used in the form of counseling and interviews. As a result of this activity, officers better understand how to use the BPJS P-Care application.